THE URGENCY OF DERADICALIZATION MEASURES FOR TERRORISM INMATES IN CORRECTIONAL FACILITIES - Irfan Irfan (Universitas 17 Agustus 1945 Semarang, 2023)
Terrorism crimes pose a threat to the state ideology, national security, state sovereignty, human values, and various aspects of societal, national, and state life, and they often have a transnational nature. These terrorism crimes require deradicalization measures for terrorism inmates in Indonesia, taking into account the individual conditions of each perpetrator, their families, and their social environment. The problem addressed in this paper pertains to the urgency of deradicalization measures for terrorism inmates in correctional facilities. This paper adopts an empirical juridical approach, conducting field research that examines legal regulations combined with data and behavior prevalent in society. The research findings indicate that: (1) The implementation of deradicalization measures for terrorism inmates in correctional facilities is not yet effective due to internal factors, which involve the lack of integration in handling terrorism inmates. Additionally, external factors, such as insufficient socialization, lack of training for officers, inadequate support facilities, budget constraints, and limited facilities in correctional facilities, contribute to the inefficiency. (2) The regulation of deradicalization for terrorism inmates in correctional facilities is based on Law Number 22 of 2022 concerning Correctional Institutions. The deradicalization regulation for terrorism inmates is stipulated in Article 54 paragraph (4), which outlines the stages: identification and assessment, rehabilitation, reeducation, and social reintegration. (3) The urgency of deradicalization measures for terrorism inmates in correctional facilities is not specific, as it is still treated similarly to other cases involving inmates. The deradicalization measures are carried out through social reintegration programs, education programs, skills training, and entrepreneurship programs for terrorism inmates, which aims to improve their well-being after their release and facilitate their reintegration into society to support their families. The independence and self-confidence of terrorism inmates in returning to society will prevent them from returning to their terrorist groups.